Middle East respiratory syndrome coronavirus (MERS-CoV) internalization does not rely on DPP4 cytoplasmic tail signaling - Karthika Thankamani; Divakar Shubham; Gayatri Kandpal; Ann Mary Isaac; Modenkattil Sethumadhavan Kavitha; V. Stalin Raj (npj Viruses)
Abstract Middle East respiratory syndrome coronavirus (MERS-CoV) infects respiratory epithelial cells in humans and camels by binding to dipeptidyl peptidase 4 (DPP4) as its entry receptor. DPP4 is a multifunctional type II membrane protein with a long ectodomain and a short six-amino-acid (aa) cytoplasmic tail. MERS-CoV is known to bind to the ectodomain of DPP4 to gain entry into the host cell. However, the role of the cytoplasmic tail in the entry process remains unclear. Here, we show that mutating or deleting individual aa residues or the entire cytoplasmic tail of DPP4 (ΔcytDPP4) does not completely prevent DPP4 from being inserted into the membrane or from allowing the binding of the MERS-CoV spike protein and pseudovirus infection. Although two mutants, ΔcytDPP4, and a single aa deleted DPP4 (ΔK6DPP4) displayed less surface presentation than wtDPP4, the spike protein could still bind and localize on different DPP4 mutants. The reduced surface expression of ΔK6DPP4 might be due to the extended transmembrane domain, which is altered by the hydrophobic tryptophan (W) residue adjacent to the deleted K6. Furthermore, HEK293T cells transiently expressing DPP4 mutants were permeable to MERS-CoV pseudovirus infection. Not only transiently expressing cells but also cells stably expressing the ΔcytDPP4 mutant were susceptible to MERS-CoV pseudoviral infection, indicating that the DPP4 cytoplasmic tail is not required for MERS-CoV entry. Overall, these data suggest that, although MERS-CoV binds to DPP4, other host factors may need to interact with DPP4 or the spike protein to trigger internalization.